2003
DOI: 10.1210/en.2002-0164
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Stimulates Intracellular Calcium Release and Mitogen-Activated Protein Kinases Via a G Protein-Coupled Receptor in Skeletal Muscle Cells

Abstract: Involvement of intracellular Ca(2+) and ERK1/2 phosphorylation in the fast nongenomic effects of androgens in myotubes was investigated. Testosterone or nandrolone produced fast (<1 min) and transient increases in intracellular Ca(2+) with an oscillatory pattern. Calcium signals were slightly reduced in Ca(2+)-free medium, but lack of oscillations was evident. Signals were blocked by U-73122 and xestospongin B, inhibitors of inositol 1,4,5-trisphosphate (IP(3)) pathway. Furthermore, IP(3) increased transiently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
179
3
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(205 citation statements)
references
References 45 publications
15
179
3
8
Order By: Relevance
“…DHT did not activate MAPK3/1 or PI3K/AKT signalling pathways in hamster Leydig cells (results not shown). Although testosterone failed to activate PI3K/AKT (results not shown), this androgen induced a rapid phosphorylation of MAPK3/1 within short-term incubations (1-3 min), which was also detected after 2-3 h. These results are similar to those observed in studies performed in breast cancer, skeletal muscle cells, prostate stroma cells and Sertoli cells in which androgen activates MAPK3/1 too quickly to be explained by the classical androgen receptor pathway (Peterziel et al 1999, Zhu et al 1999, Estrada et al 2003, Fix et al 2004, Rahman & Christian 2007. We also found that Bi prevented the effects of testosterone on phospho-MAPK3/1 indicating that androgen receptors are required for testosterone-mediated MAPK activation.…”
Section: Testosterone Induces Testicular Ptgs2supporting
confidence: 88%
“…DHT did not activate MAPK3/1 or PI3K/AKT signalling pathways in hamster Leydig cells (results not shown). Although testosterone failed to activate PI3K/AKT (results not shown), this androgen induced a rapid phosphorylation of MAPK3/1 within short-term incubations (1-3 min), which was also detected after 2-3 h. These results are similar to those observed in studies performed in breast cancer, skeletal muscle cells, prostate stroma cells and Sertoli cells in which androgen activates MAPK3/1 too quickly to be explained by the classical androgen receptor pathway (Peterziel et al 1999, Zhu et al 1999, Estrada et al 2003, Fix et al 2004, Rahman & Christian 2007. We also found that Bi prevented the effects of testosterone on phospho-MAPK3/1 indicating that androgen receptors are required for testosterone-mediated MAPK activation.…”
Section: Testosterone Induces Testicular Ptgs2supporting
confidence: 88%
“…The use of dominant negative mutants of Ras and MEK demonstrated that androgens activate the Ras/MEK/ERK pathway (Estrada et al 2003). The actions described above were not blocked by cyproterone acetate, an inhibitor of the AR, indicating that distinct non-genomic pathways exist for the action of androgens in skeletal muscle cells (Estrada et al 2000(Estrada et al , 2003.…”
Section: Non-genomic Pathwaysmentioning
confidence: 99%
“…Although no studies have examined potential nongenomic effects of androgens on myoblasts, non-genomic pathways have been observed in rat myotubes treated with androgens (Estrada et al 2000(Estrada et al , 2003. These effects were characterized by an early increase in intracellular calcium, triggered 15-30 s after testosterone addition, preceded by an increase in inositol 1,4,5-trisphosphate (IP3) mass (Estrada et al 2000).…”
Section: Non-genomic Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations